2013
DOI: 10.1534/genetics.113.155341
|View full text |Cite
|
Sign up to set email alerts
|

Rare Variants in Hypermutable Genes Underlie Common Morphology and Growth Traits in WildSaccharomyces paradoxus

Abstract: Understanding the molecular basis of common traits is a primary challenge of modern genetics. One model holds that rare mutations in many genetic backgrounds may often phenocopy one another, together explaining the prevalence of the resulting trait in the population. For the vast majority of phenotypes, the role of rare variants and the evolutionary forces that underlie them are unknown. In this work, we use a population of Saccharomyces paradoxus yeast as a model system for the study of common trait variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 81 publications
1
15
1
Order By: Relevance
“…We found that most activators in this pathway are expressed at higher levels in S. paradoxus, while inhibitors expression is higher in S. cerevisiae ( Fig 5D). Variants of one such inhibitor, Ira2, was previously reported to be involved in morphological variation in wild S. paradoxus isolates [21], supporting the notion that these expression variations could have a large phenotypic effect.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We found that most activators in this pathway are expressed at higher levels in S. paradoxus, while inhibitors expression is higher in S. cerevisiae ( Fig 5D). Variants of one such inhibitor, Ira2, was previously reported to be involved in morphological variation in wild S. paradoxus isolates [21], supporting the notion that these expression variations could have a large phenotypic effect.…”
Section: Discussionmentioning
confidence: 60%
“…Still, evolutionary related species that express the same set of proteins differ in complex phenotypes, allowing non-motile cells to forage for nutrients [17][18][19]. By contrast, S. paradoxus (CBS432), a close relative of S. cerevisiae, becomes filamentous even in rich media [20,21]. Therefore, the two species activate distinct differentiation programs when presented with the same condition, providing a model for evolutionary recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…The IRA2 allele of MS164 has an insertion of eight nucleotides at position 820 of 9248 nucleotides, creating a stop codon at position 880, and thus likely encoding a strongly truncated inactive protein. Although IRA2 likely constitutes the causative allele in the gene block 3 in view of the frameshift mutation and the previous reports linking IRA2 polymorphisms to differences in stress tolerance [42,[63][64][65][66][67][68], its involvement appears more complex with possible interaction with one or more neighboring genetic elements.…”
Section: Gene Block 3 Qtl4mentioning
confidence: 93%
“…Significantly, we have shown previously that IRA1/2 and MTH1 mutations can arise in the same background, and attain high frequency [46]. It is noteworthy that allelic variation at IRA1 and IRA2, which are homologs of the hypermutable human neurofibromatosis gene NF1 , results in diverse morphological and growth phenotypes in Saccharomyces paradoxus [50]. …”
Section: Resultsmentioning
confidence: 99%